(untitled) (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to provide basic data for improving the desirable nursing image by identifying subjectivity of the nursing image of Korean small and medium-sized hospitals. Method: Final 57 Q-sample constructed of 267 Q-populations. P-sample collected by convenience sampling of 36 nurse in Korean hospitals. P-sample collection was from August 25, to 2017 September 15. Data analysis of the principal component factor analysis method based on PC-QUANL use Findings: Results of this study among the small-medium sized hospital’s nurses, three types of attitudes toward nursing images were identified: Type 1 (Caring provider with a mission); Type 2 (Professional health manager); and Type 3 (Responsible medical profession). Improvements/Applications: The results of this study can be helpful in understanding the nursing image and this can be used as basic data for the establishment of desirable nursing image.